Graphene-Encapsulated Si on Ultrathin-Graphite Foam as Anode for High Capacity Lithium-Ion Batteries - Ji, Junyi; Ji, Hengxing; Zhang, Li Li; Zhao, Xin; Bai, Xin; Fan, Xiaobin; Zhang, Fengbao; Ruoff, Rodney S. (Advanced materials (Weinheim), 2013)
A Si/graphene composite is drop‐casted on an ultrathin‐graphite foam (UGF) with three dimensional conductive network. The Si/graphene/UGF composite presents excellent stability and relatively high overall capacity when tested as an anode for rechargeable lithium ion batteries.